2010
DOI: 10.1002/ejlt.201000326
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of extracts from six different Sudanese plant materials

Abstract: Methanolic extracts obtained by manual solvent extraction (MSE) and accelerated solvent extraction (ASE) of different Sudanese plant materials (Sclerocarya birrea leaves, Salvadora persica bark and leaves, Combretum hartmannianum leaves, Guiera senegalensis leaves and roots) were investigated for their antioxidant activity. There was no significant difference between the two extraction methods ( p < 0.01) regarding the total amount of phenolic compounds expressed as gallic acid equivalents (GAE) (52.6-166.7 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…An induction period of 4.02 h for sunflower oil mixed with purified extract was reported as compared to 2.26 h for sunflower oil (Electronic supplementary material Figure S3(a) and (b)).The large induction time represents higher antioxidant activity. Taha et al. (2010) and Sun and Ho (2005) also found a similar trend while studying antioxidant activity of different plant materials.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…An induction period of 4.02 h for sunflower oil mixed with purified extract was reported as compared to 2.26 h for sunflower oil (Electronic supplementary material Figure S3(a) and (b)).The large induction time represents higher antioxidant activity. Taha et al. (2010) and Sun and Ho (2005) also found a similar trend while studying antioxidant activity of different plant materials.…”
Section: Resultssupporting
confidence: 61%
“…Oxidative stability was determined using Rancimat tubes containing 2 g of each mixture. Experiments were performed at 120 ℃ for 20 h using Rancimat (Metrohm, Switzerland) instrument (Sun and Ho, 2005; Taha et al., 2010). Air supply was maintained at 20 l h −1 .…”
Section: Methodsmentioning
confidence: 99%
“…They were found to be 105.90, 129.10 and 62.90 mg GAE/g extract in the Gezira sample, respectively. Another study found that the amount of total extractable phenolics from bark and leaves of Salvadora persica was 52, 6 and 166, 7 mg GAE/ g DW, respectively (Taha et al, 2010).…”
Section: Total Phenolic Contentmentioning
confidence: 96%
“…39 Concerning Taha et al, they found that the amount of the total extractable polyphenol from the bark and leaves of S. persica was 52.6 and 166.7 mg of GAE/g of DW, respectively. 40 The total flavonoid concentrations present in the EES and EEC were 52.12 + 2.32 mg of QE/g of S. persica and 43.62 + 5.90 mg of QE/g of composite, respectively. The ratios of total flavonoids/ total polyphenol in S. persica (0.59) and in the composite (0.61) indicate high proportions of flavonoids.…”
Section: Antioxidant Activity Of Elaborated Compositementioning
confidence: 92%